Analysis of vaccine messages on social media (Twitter) in Scandinavia - H. Fues Wahl; B. Wikman Erlandson; C Sahlin; M. Nyaku; G. Bencina (Taylor & Francis Group, 2022)
Vaccine hesitancy is listed as one of the top 10 global health threats by the WHO. Existing studies investigating the relationship between vaccine hesitancy and social media have found that misinformation and vaccine concerns on social media can cause significant declines in vaccine coverage rates. The objective of this study was to provide insight into the dynamics of vaccine messages on Twitter in Scandinavia (Denmark, Norway, Sweden), by analyzing tweets in local languages during 2019. A validated measure, the 5C scale, was used to map relevant predictors of vaccination behavior, capturing the factors confidence (in vaccines and the system that delivers them), complacency (not perceiving diseases as high risk), constraints (structural and psychological barriers), calculation (engagement in extensive information searching) and collective responsibility (willingness to protect others). A total of 1794 tweets met the inclusion criteria (DK: 48%, NO: 15%, SE: 37%), predominantly tweeted by private users (86%). The HPV vaccine was mentioned in 81% of tweets. Tweets were classified as expressing confidence (61%), complacency (18%), constraints (15%), calculation (15%), and collective responsibility (4%). Confidence in vaccines and the system that delivers them was expressed in 57%. A lack of confidence was expressed in 4% of all tweets, in combination with calculation in 39%. Analyzing public sentiment toward vaccination on Twitter is a useful tool to leverage for better understanding of the dynamics behind vaccine hesitancy. This analysis could provide actionable information for healthcare professionals and public health authorities to mitigate online misinformation and public vaccine concerns.